Protection practices for trench and excavation in Quebec sensitive clay soils: Review of codes, guidelines, and research needs. (November 2020) - Alam, Miah; Chaallal, Omar; Galy, Bertrand
Highlights: Cave-ins are still frequent in the construction industry and present a serious risk for workers. A comparison of jurisdictions and construction guidelines is presented. A review of recent research work on cave-in risks with finite element analyses is presented. Based on those, research needs for sensitive clay cave-in risks are proposed. Abstract: Cave-ins are very frequent in the construction industry and present a very serious risk for workers who operate inside trenches or excavations. Studies show that excavations or trenches in Quebec sensitive clay soils are extremely hazardous due to possible severe and sudden loss of soil shear strength. Many North American and European construction safety authorities have already adopted proper methods and excavation protection practices according to their soil classification. This paper reviews existing construction codes and guidelines, as well as published research studies related to worker safety and protection in excavations and trenches in sensitive clay soil. The paper also discusses the needs for research on prevention strategies to eliminate potential cave-in risk sources from occurring in Quebec sensitive clay soil.